2008
DOI: 10.1093/pcp/pcn125
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of DEAD-Box RNA Helicases in Arabidopsis thaliana under Abiotic Stress Conditions

Abstract: DEAD-box RNA helicases have been implicated to have a function during stress adaptation processes, but their functional roles in plant stress responses remain to be clearly elucidated. Here, we assessed the expression patterns and functional roles of two RNA helicases, AtRH9 and AtRH25, in Arabidopsis thaliana under abiotic stress conditions. The transcript levels of AtRH9 and AtRH25 were up-regulated markedly in response to cold stress, whereas their transcript levels were down-regulated by salt or drought st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 35 publications
2
60
0
1
Order By: Relevance
“…4 B-D). The importance of the MRH4-like RNA helicase for growth at cold temperature in N. crassa is consistent with work on RNA helicases in many other systems (40,46,47), although the relatively modest effect of deleting this locus may be a consequence of functional redundancy among the 18 known helicases in the N. crassa genome, as has been suggested in Arabidopsis (47).…”
Section: Genes Inside Divergence Islands Have Functions and Patterns Ofsupporting
confidence: 84%
“…4 B-D). The importance of the MRH4-like RNA helicase for growth at cold temperature in N. crassa is consistent with work on RNA helicases in many other systems (40,46,47), although the relatively modest effect of deleting this locus may be a consequence of functional redundancy among the 18 known helicases in the N. crassa genome, as has been suggested in Arabidopsis (47).…”
Section: Genes Inside Divergence Islands Have Functions and Patterns Ofsupporting
confidence: 84%
“…DEAD-box RNA helicases have been implicated to have a function during stress adaptation processes, but their functional roles in plant stress responses remain to be clearly elucidated (Owttrim, 2006). Kim et al (2008) found differential expression in transcript levels of two RNA helicases viz. AtRH9 and AtRH25 in Arabidopsis thaliana exposed to cold, drought or salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…RH7 plays a role in pre-18S rRNA processing and small ribosome subunit biogenesis, and promotes plant development at low temperatures Liu et al, 2016). The cytosolic RH5, RH9, and RH25 helicases are involved in the response to both salt and cold stresses (Kant et al, 2007;Kim et al, 2008), whereas the plastid-localized RH3, which is required for intron splicing, mediates salt-and cold-stress responses (Larkin et al, 2003;Gu et al, 2014). Moreover, RH50 associates with RNA-containing megadalton complexes that are RNase-sensitive and contain ribosomal proteins, suggesting that RH50 interacts with immature chloroplast ribosomes, possibly as a ribosomal biogenesis factor.…”
Section: Rh50 and Gun1: Coexpression And Colocalizationmentioning
confidence: 99%
“…In fact, the cytosolic RH7, which is involved in pre-18S rRNA processing and biogenesis of the small (40S) ribosomal subunit, is essential for plant development at low temperatures Liu et al, 2016). Moreover, the helicases RH5, RH9, and RH25 contribute to the response to salt and cold stresses (Kant et al, 2007;Kim et al, 2008), and the plastidlocated RH3, which is required for intron splicing, mediates salt-and cold-stress responses (Gu et al, 2014).…”
Section: Rh50 Promotes Biogenesis Of the Plastid Ribosome Bymentioning
confidence: 99%